Recent Advances in Iron-Containing Perovskites for Supercapacitors - Avcioglu, Celal; Avcioglu, Suna (WILEY-V C H VERLAG GMBH, 2025)
The growing energy demands in transportation and portable electronics necessitate advancements in energy storage technologies. Supercapacitors, with their exceptional power density, rapid charge-discharge capabilities, and long cycle life, provide a compelling solution for energy storage applications. However, their inherent low energy density remains a persistent challenge. To overcome this limitation, perovskite oxides, particularly those containing iron, have emerged as promising electrode materials. These materials leverage their unique structure, compositional flexibility, rich redox chemistry, and pseudocapacitive attributes. This concise overview aims to provide insights into the development of iron-containing perovskite oxides and their design principles. The discussion covers fundamental aspects of supercapacitors, iron-containing perovskite structures, synthetic methodologies, defect engineering, and the construction of composites. The overview concludes by providing a perspective, particularly regarding the challenges in designing efficient and stable supercapacitors based on iron-containing perovskite oxides.
Keywords: electrodes; energy storage; intercalation pseudocapacitance; iron-based perovskites; supercapacitors; TIO2 NANOTUBE ARRAYS; ELECTROCHEMICAL PROPERTIES; BISMUTH FERRITE; NANOFIBERS; MORPHOLOGY; REDUCTION; EVOLUTION; TRANSPORT; STORAGE; Science & Technology - Other Topics; Energy & Fuels; Materials Science